(untitled) (The International Journal for Scientific Research, 2024)
The aim of this study was to investigate the impact of schedule crashing on project performance: an application to construction projects in the Riyadh region. Schedule crashing is an important technique used to accelerate project completion, but it can have negative effects if not managed properly. The study focuses on five key aspects of project performance: duration, cost, scope, quality, and stakeholder satisfaction. The study adopted a descriptive-analytical methodology and used a questionnaire as a tool for collecting primary data. The questionnaire was distributed to a random sample from the research community, which included engineers working on construction projects in the Riyadh region of Saudi Arabia. A total of 436 questionnaires were obtained, and after inspection and verification, 390 valid questionnaires were analyzed. The data was analyzed, and the hypotheses were tested using SPSS software. The results showed a statistically significant impact of schedule crashing on project performance, affecting duration, cost, scope, quality, and stakeholder satisfaction. The study provided several recommendations to improve schedule crashing management and reduce negative impacts.